BUILDING TRUST THROUGH CONTRACT: A LEGAL PROTECTION EFFORT FOR SERVICE PROVIDERS AND USERS IN THE DIGITAL ERA: BUILDING TRUST THROUGH CONTRACT: A LEGAL PROTECTION EFFORT FOR SERVICE PROVIDERS AND USERS IN THE DIGITAL ERA - Hafizh, Deri; Anggraeni, Dewi; Rungsimanop, Hattarawadee (PENA LAW: International Journal of Law, 2024)
This study investigates the effectiveness of mediation as a mechanism for resolving business disputes in Indonesia, focusing on its procedural efficiency and impact on the relationships between disputing parties. Employing a qualitative research approach with descriptive normative analysis, the research highlights the legal foundations of mediation established by laws such as Law No. 30 of 1999 and Supreme Court Regulation No. 1 of 2016, which mandate mediation prior to litigation. The findings reveal that while mediation presents significant benefits, including faster resolution times and cost savings, its effectiveness is contingent on several factors: public awareness, the quality of mediators, and the parties' willingness to engage collaboratively. The study emphasizes the importance of confidentiality, neutrality, and mutual interest as key principles in ensuring a fair mediation process. Despite the challenges faced, such as a preference for litigation and uncertainties regarding the enforcement of mediated agreements, the research indicates that mediation has the potential to enhance business relationships and streamline dispute resolution processes. The insights gleaned from this study not only contribute to the understanding of mediation within the Indonesian legal context but also offer valuable lessons for other jurisdictions aiming to develop their alternative dispute resolution frameworks.